Kepastian Hukum Hak Guna Usaha di atas Hak Pengelolaan - Nisriina Milla Sharfinda; Antikowati Antikowati; Bhim Prakoso (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2023)
The ratification of Law 6/2023 creates a new norm for granting HGU, which is stated in Article 129 Paragraph (2) that the right: to cultivate; build use; and use, can be provided on top of HPL. Based on the closing provisions of Law 6/2023 Article 184 which states that all implementing regulations remain in force as long as they do not conflict with government regulations in place of this law, PP 18/2021 is still valid. The government regulation states that in Article 8 Paragraph (1) HPL can be granted HGU. This can result in abuse of authority as has occurred in the general transmigration program for West Java residents to Riau Province in East Tambusai Village, Kampar Regency, the Regional Government of Riau Province part of the transmigration management land was carried out in collaboration with PT Pancasurya Agrindo. The research carried out was to analyze the implementation of granting HGU applications above HPL to determine the basis and legal certainty of HGU above HPL. This research using the normative juridical research method found the problem related to the basis and the legal certainty of HGU above HPL. Legal certainty from HGU above HPL is not optimal if based on the analysis of existing cases, because the application article for the issuance of HGU above HPL does not provide space for people who object to the issuance of HGU certificates. Legal certainty will be implemented if the law related to the implementation of HGU above HPL is effective.